2018
DOI: 10.1182/blood-2017-05-786947
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 1 is a therapeutic target in chronic lymphocytic leukemia

Abstract: Casein kinase 1δ/ε (CK1δ/ε) is a key component of noncanonical Wnt signaling pathways, which were shown previously to drive pathogenesis of chronic lymphocytic leukemia (CLL). In this study, we investigated thoroughly the effects of CK1δ/ε inhibition on the primary CLL cells and analyzed the therapeutic potential in vivo using 2 murine model systems based on the Eµ-TCL1-induced leukemia (syngeneic adoptive transfer model and spontaneous disease development), which resembles closely human CLL. We can demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 70 publications
5
39
0
Order By: Relevance
“…A very recent study demonstrated that CK1ε/δ is a novel therapeutic target in chronic lymphocytic leukemia (CLL). The CK1ε/δ inhibitor PF-670462 significantly blocked microenvironmental interactions of CLL cells and delayed leukemia development and progression in the Eμ-TCL1 mouse model ( 58 ). In this study, CK1ε and CK1δ have been identified as distinctive intracellular targets of tumor-promoting TPA.…”
Section: Discussionmentioning
confidence: 99%
“…A very recent study demonstrated that CK1ε/δ is a novel therapeutic target in chronic lymphocytic leukemia (CLL). The CK1ε/δ inhibitor PF-670462 significantly blocked microenvironmental interactions of CLL cells and delayed leukemia development and progression in the Eμ-TCL1 mouse model ( 58 ). In this study, CK1ε and CK1δ have been identified as distinctive intracellular targets of tumor-promoting TPA.…”
Section: Discussionmentioning
confidence: 99%
“…However, off-target effects due to direct binding to microtubules and due to blockage of voltage-gated sodium channels can also be triggered by IC261 [9,10]. In cell culture and mouse models for chronic lymphocytic leukemia (CLL), treatment with the CK1δ-and ε-specific inhibitor PF-670462 resulted in a longer overall survival [11]. Inhibitor PF-4800567 showed increased selectivity toward CK1ε compared to CK1δ and induced remarkable anti-proliferative effects in different cell lines [12].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown earlier that in these malignancies the non-canonical Wnt pathway and BCR signaling can be targeted in a combinatorial manner. Namely, it has been observed in vivo in the mouse models of CLL where BTK inhibitor ibrutinib and anti-ROR1 antibody 45 or casein kinase 1 (CK1) inhibitors 46 showed synergistic effects. Similar behavior has been observed by Karvonen and colleagues in the in vitro model of MCL 15 .…”
Section: Discussionmentioning
confidence: 99%